Tissue engineering – nanomaterials in the musculoskeletal system (Swiss Medical Weekly, 2012)
The musculoskeletal tissues bone, cartilage and ligament/tendon are highly structured nanocomposites consisting of nanofibres embedded in a matrix of different composition. Thus, it was a logical step that during the hype of nano in the last decade, nanotechnology and nanomaterials became a hot topic in the field of musculoskeletal repair. Especially the fact that using nanomaterials would encompass a biomimetic approach, thus copying nature, was promising. However, it became evident that using nanomaterials in the repair of musculoskeletal tissues had a longer history than initially thought and its way was paved with failures, which are important to remember when applying current ideas. This current opinion paper summarises some fundamental aspects of nanomaterials to be used for musculoskeletal application and discusses where this field might move to in the near future.